Fundamentals of recessed lighting - Rey-Barreau, Joseph A.; American Lighting Association (Dallas, TX : American Lighting Association)
Presents an overview of the uses of recessed lighting and how we can use it to design effective lighting solutions.
Presenter, Joe Rey-Barreau.
DVD format.
Keywords: Lighting, Architectural and decorative; Interior lighting; Dwellings -- Lighting